Pengaruh Dana Desa Terhadap Peningkatan Daya Beli Masyarakat yang Terdampak Covid-19 - Ninik Mas'adah; Devi Febrianti (Riset Manajemen dan Akuntansi, 2025)
This study was conducted to see the impact of village funds in moving forward their level of welfare as measured by people's purchasing power amid the Covid-19 pandemic using qualitative research method. The results of the study imply that village funds play an active role in improving the welfare of rural communities so that they can stimulate the circulation of money and ensure that the wheels of the economy in the village continue to run. This study had fact that the Lamongan Regency Government has made its best efforts in distributing village funds but the level of welfare and purchasing power of the community is not too significant because of the limited BLT funds disbursed by the government. The government needs re-examine the nominal amount of BLT, this has not met the government regulation that recommends a maximum BLT budget of 35% to stimulate an increase in purchasing power.